PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN INFORMASI ASIMETRI, KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (STUDI KASUS PEMERINTAH PROVINSI BANTEN) - Yulaikah, Yulaikah; Trikawati, Trikawati; Ismanti, Riffa (Universitas La Tansa Mashiro, 2023)
This research aims to examine the effect of budget participation on budgetary slack with two moderating variables, namely: information asymmetry and organizational commitment. Inconsistencies in previous studies regarding the effect of NGO participation on budgetary slack became the motivation for this research. Data was collected using a questionnaire to local government Units / OPDs in Banten Province. Respondents were selected using a purposive sampling method where officers involved in the budgeting process, of the 105 questionnaires distributed, 80 questionnaires were returned. The analysis method uses variance-based SEM using Smart PLS 3.0. The research instrument has passed the validity and reliability standards. The research results show that budget participation has an effect on budget slack. This research proves that the interaction between research and asymmetric budget participation information has a negative effect, while organizational commitment significantly budget participation in information asymmetry can increase budgetary slack, otherwise organizational commitment reduces budgetary slack.